2021
DOI: 10.3389/fonc.2021.616027
|View full text |Cite
|
Sign up to set email alerts
|

MR-Guided Radiotherapy for Liver Malignancies

Abstract: MR guided radiotherapy represents one of the most promising recent technological innovations in the field. The possibility to better visualize therapy volumes, coupled with the innovative online adaptive radiotherapy and motion management approaches, paves the way to more efficient treatment delivery and may be translated in better clinical outcomes both in terms of response and reduced toxicity. The aim of this review is to present the existing evidence about MRgRT applications for liver malignancies, discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 120 publications
0
33
0
Order By: Relevance
“…Clinical management of patients with malignant liver lesions requires advanced diagnostic and therapeutic methods. Thus, medical imaging has been profoundly integrated into the clinical decision-making and patient care processes in cases of primary and metastatic liver cancers (1,2). Currently, positron emission tomography/computed tomography (PET/CT) has been widely used in solid neoplasm detection and staging (3), including liver malignancies (4), demonstrating higher accuracy in the tumor, node, metastasis (TNM) staging than the single modality of CT or PET (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical management of patients with malignant liver lesions requires advanced diagnostic and therapeutic methods. Thus, medical imaging has been profoundly integrated into the clinical decision-making and patient care processes in cases of primary and metastatic liver cancers (1,2). Currently, positron emission tomography/computed tomography (PET/CT) has been widely used in solid neoplasm detection and staging (3), including liver malignancies (4), demonstrating higher accuracy in the tumor, node, metastasis (TNM) staging than the single modality of CT or PET (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In SBRT, the image guidance techniques using fiducials, surface guidance, stereotactic X-ray, CT, and MRI can allow a precise identification and verification of target before and/or during treatment and also reduce the target volume by minimizing the PTV margin (26,28,29,38). MRI guidance technology is more helpful for tumors in the liver, frequently poorly visualized on the CT images, than those in other anatomical sites (28). To date, MRI guidance technology has not been applied to PBT in clinical practice, but several dosimetric studies comparing PBT with radiotherapy with X-rays in primary liver tumors showed that PBT can reduce the irradiated volume of remaining liver and allow dose escalation for tumors (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…With technological advances in radiotherapy, SBRT has a growing role as non-invasive treatment option in the treatment for patients with metastatic liver tumors (26,28,29). In particular, the recent introduction of magnetic resonance imaging (MRI) guided radiotherapy has made it possible to precisely identify and verify the target before and/or during treatment (28). Although MRI guidance technology has not been applied to PBT yet, PBT has the potential to allow safe dose escalation in the target volumes while sparing uninvolved liver tissue due to the unique property of proton beams (called 'Bragg peak') when compared to radiotherapy with X-ray; moreover, PBT has been proven to be safe and effective as a local treatment for primary liver cancer (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] SBRT requires accurate evaluation of tumor position; however, implementing it more broadly for abdominal and pelvic tumors is limited by the risk of injuring serially functioning normal tissues such as the stomach, duodenum, and small bowel. [5][6][7][8] Tumors in the abdomen/pelvis are dynamic, exhibiting positional changes relative to organs-at-risk (OARs) due to respiratory motion, peristalsis, and intrinsic deformation. [9][10][11] Minimizing positional and anatomic uncertainties with computed tomography (CT) image guidance has provided a stepwise improvement in tumor localization and radiation delivery.…”
Section: Introductionmentioning
confidence: 99%